Electrocardiographic changes in diabetes mellitus - Kittnar, O (Physiological research, 2015)
Diabetes mellitus (DM) has been known for many years to be associated with poor cardiovascular prognosis. Due to the sensitive neuropathy, the coronary artery disease in diabetic patients is frequently asymptomatic. Also twelve leads resting ECG can be within normal limits even in an advanced stage of coronary artery disease. Therefore in addition to the standard ECG other electrocardiographic procedures started to be studied in order to find some typical signs of myocardial damages caused by DM. Repeatedly reported results showed in DM patients without cardiovascular complications the tachycardia, shortening of the QRS and QT intervals, increase of the dispersion of QT interval, decreased amplitudes of depolarization waves, shortened activation time of ventricular myocardium and a flattening of T waves confirmed by the lower value of maximum and minimum in repolarization body surface isopotential maps. Most of these changes are even more pronounced in patients with cardiac autonomic neuropathy. Comparison with similar ECG changes in other diseases suggests that the electrocardiographic changes in DM patients are not specific and that they are particularly caused by an increased tone of the sympathetic nervous system what was indirectly confirmed by the heart rate variability findings in these patients.
Keywords: sympatický nervový systém; srdce; Predictive Value of Tests; Humans; Diabetes Complications; zvířata; srdeční arytmie; Electrocardiography; Action Potentials; elektrokardiografie; Heart; komplikace diabetu; Heart Rate; Animals; lidé; Arrhythmias, Cardiac; srdeční frekvence; Sympathetic Nervous System; prediktivní hodnota testů; akční potenciály